Evaluasi Situs Web dengan Metode Cognitive Walkthrough, Heuristic Evaluation, dan User Experience Questionnaire - Putu Bagus Kresna Putrawan; I Made Candiasa; Luh Joni Erawati Dewi (Universitas Budi Darma, 2026)
The Bali High Prosecutor’s Office website, a legal service channel in Bali, has not been evaluated since 2018. A preliminary study revealed several user complaints regarding malfunctioning crucial features, such as confusing workflows and unclear guidance. This can be hindering public access to the legal process in seeking justice. To this purpose, the website’s features were evaluated through research using cognitive walkthrough, heuristic evaluation, and User Experience Questionnaire (UEQ). The evaluation process involved 10 general users to measure task scenario performance, 3 experts to identify qualitative issues, and 23 questionnaire respondents to measure user experience perceptions. The evaluation was conducted in three stages: initial design evaluation, prototype development, and final design evaluation. The initial design usability test revealed significant issues. There were numerous failures in executing task scenarios in the public complaints feature, with an average severity rating of 3,27, which is in the critical category. Furthermore, clarity and accuracy were rated below average, with 50% of the products in the dataset performing worse than the Bali High Prosecutor’s Office website. This research aims to produce evidence-based interface design recommendations capable of improving the digital service quality of the Bali High Prosecutor’s Office. The contribution of this research lies in the development and validation of a high-fidelity prototype, which was evaluated using UEQ and demonstrated significant improvement across all aspects of user experience: attractiveness, clarity, efficiency, accuracy, stimulation, and novelty. This research provides a comprehensive evaluation framework adoptable by other government agencies seeking to enhance their digital public services